Reach, Benefit, Empower: Indicators for measuring impacts of programs and policy towards gender equality - Quisumbing, Agnes R. (International Food Policy Research Institute, 2017)
Presented by Agnes Quisumbing (IFPRI), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.